2011
DOI: 10.4103/2229-5151.79276
|View full text |Cite
|
Sign up to set email alerts
|

Resource utilization in the management of traumatic brain injury patients in a critical care unit: An audit from a rural set-up of a developing country

Abstract: Background:Neurosurgical patients including patients with severe head injury are at risk of developing respiratory complications. These can adversely affect the outcome and can result in poor survival. Many studies confirm that tracheostomy is a safe, effective method of airway management for patients with severe head, facial and multisystem organ trauma.Aims:To know the indications for performing early tracheostomy and its outcome.Settings and Design:Retrospective data analysis.Materials and Methods:The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Hence, our findings are not generalizable to non-Western countries because lack of resources restricts the routine use of aggressive treatment strategies in these countries. 52 Related, our findings cannot be generalized to children because it is known that guideline adherence in children varies from guideline adherence in adults 36 and might also be influenced by other factors such as concern about radiation.…”
Section: Discussionmentioning
confidence: 85%
“…Hence, our findings are not generalizable to non-Western countries because lack of resources restricts the routine use of aggressive treatment strategies in these countries. 52 Related, our findings cannot be generalized to children because it is known that guideline adherence in children varies from guideline adherence in adults 36 and might also be influenced by other factors such as concern about radiation.…”
Section: Discussionmentioning
confidence: 85%
“…In patients on mechanical ventilation, tracheostomy may facilitate weaning from the ventilator, decrease length of intensive care unit (ICU) or hospital stay, and improve pulmonary toilet 3,4 . Many studies have confirmed that tracheostomy is a safe, effective method of airway management for patients with severe head, facial and multisystem organ trauma 5 . If performed appropriately in a setting with adequate resources, it is associated with a low complication rate 6 .…”
Section: Introductionmentioning
confidence: 99%